Campaign communication and political marketing - Maarek, Philippe J. (Wiley-Blackwell, 2011)
"Campaign Communication and Political Marketing is a comprehensive, internationalist study of the modern political campaign. It indexes and explains their integral components, strategies, and tactics.. Offers comparative analyses of campaigns from country to country. Covers topics such as advertising strategy, demography, the effect of campaign finance regulation on funding, and more. Draws on a variety of intenational case studies including the campaigns of Barack Obama and Nicolas Sarkozy. Analyses the impact of digital media and 24/7 news cycle on campaign conduct"